2020
DOI: 10.1038/s41598-020-79071-x
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-lymphocyte ratio is an independent predictor for survival outcomes in cervical cancer: a systematic review and meta-analysis

Abstract: This updated meta-analysis sought to explore whether pretreatment neutrophil-to-lymphocyte ratio (NLR) could serve as an independent predictor for survival outcomes in patients with cervical cancer. We searched PubMed, Embase, Web of science and Scopus for studies on the association of pretreatment serum NLR with overall survival (OS) and progression-free survival (PFS) among patients with cervical cancer. Included studies with a hazard ratio (HR) and 95% confidence interval (CI) or a p-value were weighted by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 47 publications
1
20
0
Order By: Relevance
“…[29][30][31] A meta-analysis of 14 studies comprising 6041 patients with cervical cancer (SCC and adenocarcinoma) demonstrated that an elevated NLR was associated with short PFS and OS. 32 Our study showed that a high NLR was associated with short PFS and OS. Although the mechanism underlying the poorer outcomes of increased NLR has not been clarified, neutrophils have been shown to suppress the activity of lymphocytes and T cell response.…”
Section: Discussionmentioning
confidence: 51%
“…[29][30][31] A meta-analysis of 14 studies comprising 6041 patients with cervical cancer (SCC and adenocarcinoma) demonstrated that an elevated NLR was associated with short PFS and OS. 32 Our study showed that a high NLR was associated with short PFS and OS. Although the mechanism underlying the poorer outcomes of increased NLR has not been clarified, neutrophils have been shown to suppress the activity of lymphocytes and T cell response.…”
Section: Discussionmentioning
confidence: 51%
“…NLR and PLR can be easily calculated from the routine blood cell count and are more stable and predictive than each parameter alone. Similar to NLR, PLR served as a novel marker of systemic inflammation, and both biomarkers were shown to be independently related to other inflammatory markers [ 16 ] and composite adverse outcomes in various diseases, such as chronic obstructive pulmonary disease [ 17 ], metastatic renal cell carcinoma [ 18 ], non-small-cell lung cancer [ 19 ], and cervical cancer [ 20 ]. Furthermore, NLR and PLR could also predict the presence of proteinuria [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor-induced neutrophilia and thrombocytosis, which may be considered a sign of systemic inflammation, and relative lymphocytopenia, which occurs as part of the antitumor immune response, are frequently observed [47]. In a meta-analysis, an elevated pretreatment neutrophil to lymphocyte ratio was confirmed as an independent predictor of a decreased OS and PFS, regardless of stage or primary treatment [48]. In addition, a systemic immune inflammation index based on peripheral neutrophil, lymphocyte and platelet counts was established in cervical cancer patients after primary surgery.…”
Section: Hematological Parametersmentioning
confidence: 98%